A cobalt solvent extraction investigation in Africa?s Copper Belt - T. Könighofer (The Southern African Institute of Mining and Metallurgy, 2009)
Processing of copper-cobalt orebodies in Africa?s Copper Belt has received much recent attention with various flowsheet options being developed specifically for the refining of cobalt. The upfront leach and copper refining routes are well understood whereas the refining of cobalt is more complex, requiring numerous impurity removal steps to produce high purity metal. This paper describes an investigation into one of the possible processing steps in the refining of cobalt, namely, cobalt solvent extraction. The paper emphasizes the importance of upstream impurity removal to achieve the required cobalt solvent extraction feed composition. 18% (v/v) Cyanex 272 in an aliphatic diluents is used as the organic phase. The pH profiles in the various stages are evaluated in order to obtain a raffinate containing <10mg/l cobalt and with a low magnesium content reporting to the stripping section. The pH profile is also used to minimize the impurity deportment to the cobalt electrolyte. The effect of adding a pre-neutralization stage before feeding the organic phase to the extraction circuit is investigated. Zinc build-up in the stripping stages is also looked at. It is recommended for the purpose of this study that four extraction stages at an O:A ratio of 1 with a pH profile from 4.9 to 5.7 be employed. The pH is controlled with 40g/l NaOH. A pre-neutralization stage is required, where the organic phase is contacted with 10 M NaOH. Two scrubbing stages are recommended at an O:A ratio of 40, using the cobalt electrowinning advance electrolyte as the scrub liquor. Three strip stages are to be employed at an O:A ratio of 0.67.